Frank Speck and the Moisie River Incident: Anthropological Advocacy and the Question of Aboriginal Fishing Rights in Quebec - Pulla, Siomonn P. (Anthropologica, 2022)
This article examines Frank Speck’s role as a mediator of Aboriginal resource rights in early 20th-century Canada. I examine how Speck’s role as an ethnologist was deeply informed by his role as an advocate. Similarly, I will show how the work he carried out as an advocate was informed by the ethnological data he collected. I explore an incident that occurred while Speck was working in the field in 1912, within the context of the development of colonial regulations to control and administer a national fisheries policy in Canada and Quebec during the 19th century. I illustrate why traditional Aboriginal patterns of land-use and conservation were in opposition to the increasing presence of colonial regimes and their administration and regulation of a growing salmon fishery in Quebec. I draw connections between the history of this conflict and the emerging science of anthropology in the early 20th century, exploring the relationship between ethnology and advocacy during the early years of anthropology in Canada.